2017
DOI: 10.1177/014556131709600313
|View full text |Cite
|
Sign up to set email alerts
|

Laryngoceles: Concepts of Diagnosis and Management

Abstract: A laryngocele is an abnormal dilatation of the laryngeal saccule. It is a rare benign lesion of the larynx. Various modalities of treatment have been advocated for its management. We present our treatment results and outcomes of a series of cases of laryngoceles and discuss the concepts of their management. This study included patients with different laryngocele types. Patients with an internal laryngocele underwent endoscopic CO 2 laser resection, while those with a combined laryngocele underwent resection vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…The combined approach involved internal endoscopic laser resection, with a variety of open surgical approaches including a midline transcervical incision or V-shaped lateral thyrotomy. 2 , 12 However, Martinez et al. 5 reported on two cases with combined-type laryngocele who were managed solely with endoscopic laser resection.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The combined approach involved internal endoscopic laser resection, with a variety of open surgical approaches including a midline transcervical incision or V-shaped lateral thyrotomy. 2 , 12 However, Martinez et al. 5 reported on two cases with combined-type laryngocele who were managed solely with endoscopic laser resection.…”
Section: Resultsmentioning
confidence: 99%
“…7,[9][10][11] Laryngocele was treated by thyrotomy. 2,12 However, Martinez et al 5 reported on two cases with combined-type laryngocele who were managed solely with endoscopic laser resection. There were no reported complications associated with either approach, and only one post-mortem death, secondary to airway obstruction due to a combined laryngocele.…”
Section: Laryngocele Managementmentioning
confidence: 99%
See 3 more Smart Citations